2020
DOI: 10.1021/acs.jced.9b01039
|View full text |Cite
|
Sign up to set email alerts
|

Vapor–Liquid Equilibrium of Ionic Liquid 7-Methyl-1,5,7-triazabicyclo[4.4.0]dec-5-enium Acetate and Its Mixtures with Water

Abstract: Ionic liquids have the potential to be used for extracting valuable chemicals from raw materials. These processes often involve water, and after extraction, the water or other chemicals must be removed from the ionic liquid, so it can be reused. To help in designing such processes, we present data on the vapor–liquid equilibrium of the system containing protic ionic liquid 7-methyl-1,5,7-triazabicyclo[4.4.0]­dec-5-enium acetate, water, acetic acid, and 7-methyl-1,5,7-triazabicyclo[4.4.0]­dec-5-ene. Earlier stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 108 publications
1
13
0
Order By: Relevance
“…However, when water is present this is not observed, and the sample with excess acetic acid had a lower density than that with an equimolar ratio of acid and base. This is similar to the behavior observed with the vapor-liquid equilibrium data [12]. It has also been shown that protic ionic liquids, such as mTBD acetate, exhibit a reactive azeotrope (or possibly a complex) at a composition where there is an excess of acid, and the higher density at the composition where x acid equals 0.6 and x water is 0 may be due to the same intermolecular interactions that cause the azeotrope [9,10,23].…”
Section: Densitysupporting
confidence: 78%
See 4 more Smart Citations
“…However, when water is present this is not observed, and the sample with excess acetic acid had a lower density than that with an equimolar ratio of acid and base. This is similar to the behavior observed with the vapor-liquid equilibrium data [12]. It has also been shown that protic ionic liquids, such as mTBD acetate, exhibit a reactive azeotrope (or possibly a complex) at a composition where there is an excess of acid, and the higher density at the composition where x acid equals 0.6 and x water is 0 may be due to the same intermolecular interactions that cause the azeotrope [9,10,23].…”
Section: Densitysupporting
confidence: 78%
“…To our knowledge, no other articles have investigated how changes in the acid-to-base ratio affect the density of the overall solution. This article is a continuation of our earlier research, which presented data on the vapor-liquid equilibrium of the same system [12].…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations